Perilaku Memilih Masyarakat Desa dalam Pemilihan Kepala Desa di Desa Purwobinangun Kecamatan Sei Bingai Kabupaten Langkat - Jojor Mindo Manullang; Ivana Theo Philia; Laras Sati Sintania; Julia Ivanna (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research aims to analyze the voting behavior of the people of Purwobinangun Village in the village head election, considering the influencing factors, decision-making processes, and obstacles faced. This study uses a qualitative descriptive approach, through interviews, observations, and documentation from various informants in Purwobinangun Village, Sei Bingai District, Langkat Regency. The research results show that the selection behavior of the people of Purwobinangun Village is influenced by various factors. This research provides a comprehensive understanding of the dynamics of voting behavior in rural communities, integrating sociological, psychological, and rational aspects. The results are expected to be useful for prospective village heads and success teams in developing more transparent and realistic campaign strategies, for local governments in improving political literacy and providing comprehensive information, and for the community to be more proactive in seeking information and considering choices rationally.